2019
DOI: 10.1016/j.rbo.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Anastomose de Riché-Cannieu: estrutura, função e significância clínica

Abstract: Objective  To define the anatomy pattern and the incidence of Riché-Cannieu anastomosis, that is, median and ulnar communication in the palmar aspect of the hand. Materials Methods  A total of 80 anatomical dissections were performed on 60 hands of 30 cadavers from 1979 to 1982, and on 20 hands from 2012 to 2015. All of these procedures were performed at the Department of Anatomy of our institution. The incidence of Riché-Cannieu anastomosis and the innervation of the thenar muscles were studied. Results  Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 9 publications
(30 reference statements)
0
19
0
5
Order By: Relevance
“…Some studies have reported rates as great as 70 to 80%, which the authors emphasized could potentially be higher with finer techniques. 32,33 This belief is supported by the findings in another study by Caetano et al, 34 in which the presence of RCA was recorded in 100% of dissected fresh cadaver hands (n = 80), with the use of careful, high magnification (10-16 ×) technique. It may therefore be feasible to consider RCA as a normal anatomical neural connection.…”
Section: Riche-cannieu Anastomosismentioning
confidence: 71%
See 1 more Smart Citation
“…Some studies have reported rates as great as 70 to 80%, which the authors emphasized could potentially be higher with finer techniques. 32,33 This belief is supported by the findings in another study by Caetano et al, 34 in which the presence of RCA was recorded in 100% of dissected fresh cadaver hands (n = 80), with the use of careful, high magnification (10-16 ×) technique. It may therefore be feasible to consider RCA as a normal anatomical neural connection.…”
Section: Riche-cannieu Anastomosismentioning
confidence: 71%
“…It may therefore be feasible to consider RCA as a normal anatomical neural connection. 7,34 Further, race might factor into observed prevalence. 33,35 For example, in a study by Kimura et al 33 , African-Americans presented with RCA significantly less frequently than other racial groups, and no significant difference was found between Hispanics and Caucasians.…”
Section: Riche-cannieu Anastomosismentioning
confidence: 99%
“…The innervation variations of these small muscles are of high clinical importance because in the case of a complete lesion of the MN or UN, some of these muscles may or may not be paralyzed, possibly leading to the erroneous conclusion of a partial rather than complete lesion. 28,31 Profound knowledge of these anastomoses is essential for accurate interpretation of clinical findings and to avoid the risk of iatrogenic injuries during surgical procedures. 32…”
Section: Berrettini Anastomosismentioning
confidence: 99%
“…Carpal tunnel syndrome, in particular, has been associated with exacerbated or decreased symptoms in the presence of these anastomoses. 52,54 It can generate an "ulnar-hand" phenomenon in some cases, in which the muscles in the tenar eminence only present innervation from the ulnar nerve, with no contribution from the median nerve. 55 In an electroneuromyographic study, 56 it caused difficulty in interpreting the results, especially in the evaluation of the lesions to the median nerve, the opponens pollicis muscle, amd the abductor pollicis brevis muscle.…”
Section: Riche-cannue Anastomosismentioning
confidence: 99%